Anti-jelly positive electrode slurry and method, sodium ion battery and preparation method of sodium ion battery
By adding carboxylic acid additives to the positive electrode slurry of sodium ion battery, the problem of jelly degradation of the positive electrode material during the pulping process is solved, the stability of the slurry and the consistency of the electrode sheet coating is achieved, and the thickness of the slurry is improved, and the thickness of the slurry is improved. Battery performance and stability.
Patent Information
- Application Number
- CN202411611639.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
AI Technical Summary
The positive electrode material of sodium ion battery is easily jelly-degraded during the pulping process, resulting in poor fluidity and uneven coating of the electrode sheet, affecting the production stability and performance of the battery.
The carboxylic acid additives are added to the positive electrode slurry, and the acidic groups are gradually reacted with the alkaline components on the surface of the positive electrode material to neutralize the residual alkaline components to maintain the acid-base balance of the slurry and prevent jelly degradation.
The fluidity and stability of the slurry are achieved, the consistency of the coating surface density of the electrode sheet is significantly improved, and the rate discharge performance and cycle stability of the battery are improved.
Smart Images

Figure CN119447170A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation and application of positive electrode materials for sodium ion batteries, and in particular to a jelly-proof positive electrode slurry and a method thereof, a sodium ion battery and a preparation method thereof. Background Art
[0002] Sodium-ion batteries have attracted extensive attention in recent years in the fields of large-scale energy storage and electric vehicles due to their abundant resources, low cost, long life, and excellent comprehensive performance. Their working principle is similar to that of lithium-ion batteries. The positive electrode material is usually layered oxide (NaxMO 2 ) structure, where M is a transition metal element, has high energy density and good electrochemical performance. However, in the process of preparing the positive electrode material, since sodium oxide reacts easily with oxygen and carbon dioxide in the air, the generated NaOH and Na 2 CO 3 The residue will cause the pH value of the slurry to increase, which will cause the slurry to become jellied, resulting in poor slurry fluidity and uneven electrode coating, which will seriously affect the production stability and final performance of the sodium-ion battery.
[0003] In the prior art, in order to avoid the jelly phenomenon, organic weak acid additives are usually added to the slurry to neutralize the alkalinity of the slurry. However, while this method solves the jelly problem, it often causes new problems: 1. Capacity attenuation: Since the added organic weak acid will affect the electrochemical activity of the positive electrode material, it is difficult to fully utilize the battery capacity.
[0004] 2. Unstable acid-base balance: Acidic additives react unevenly with residual alkali in different links such as pulping, coating and rolling, resulting in difficulty in maintaining the acid-base balance of the slurry, easy stratification of the slurry, and unstable viscosity, thus affecting the quality of the electrode.
[0005] 3. Secondary reactions during high-temperature treatment: Additives may undergo secondary reactions with residual components during the high-temperature formation stage of the battery, generating uncontrollable by-products that affect the battery's internal resistance and self-discharge performance and reduce the battery's cycle stability.
[0006] To improve the above problems, the industry has also tried to improve the stability of the slurry by optimizing the slurry composition ratio, using different binders or conductive agents, etc. However, such improvements often cannot solve the fundamental problem of unstable acid-base balance, and due to the differences in chemical properties between materials, the effect of adjusting the ratio on inhibiting the jellying phenomenon of the slurry is limited; the improvement of the binder usually increases the cost and complicates the slurry preparation process.
[0007] Therefore, how to effectively stabilize the acid-base balance of the slurry, inhibit the jellying phenomenon and improve the uniformity of electrode coating has become a technical problem to be solved by the present invention. Summary of the invention
[0008] The technical problem solved by the present invention is to provide a jelly-proof positive electrode slurry and method, a sodium ion battery and a preparation method thereof in view of the defects existing in the above-mentioned prior art, so as to solve the problems of jellying and poor coating uniformity of the positive electrode slurry of the sodium ion battery during the slurrying process proposed in the above-mentioned background technology.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A jelly-proof positive electrode slurry, the positive electrode slurry is composed of an O3 type layered oxide positive electrode material, a conductive agent, a binder, a solvent and an additive, wherein the chemical formula of the positive electrode material is Na x MO 2 , 0.67 < x ≤ 1, M is at least one transition metal element including but not limited to nickel, iron, manganese, copper, titanium, and cobalt; The additive is an organic acid substance containing a carboxyl group, and its general chemical formula is R-COOH, wherein R is an alkyl group, an alkenyl group, a hydroxyl group or a keto group; The additive is added in an amount of 0.01% to 2%, preferably 0.2% to 0.5%, of the total weight of the positive electrode slurry. The additive is uniformly added to the mixed system of the O3-type layered oxide positive electrode material, the conductive agent, the binder and the solvent, so that the acidic groups in the additive gradually react with the alkaline components on the surface of the positive electrode material, thereby reducing the residual alkali content in the slurry system and maintaining the fluidity and stability of the slurry during the slurry preparation and subsequent coating process. The additive is used to maintain the acid-base balance of the slurry during the stirring and coating process, avoid the jelly phenomenon caused by pH value fluctuation, and obtain a consistent surface density on the coating surface.
[0010] As a further scheme of the present invention, the stepwise reaction means that the acidic groups in the additive first react with the alkaline components exposed on the surface of the positive electrode material during the slurry stirring process, and then gradually react to neutralize the residual alkaline components in the slurry system during the coating and rolling process to maintain the acid-base balance of the slurry, so as to maintain the fluidity of the slurry and the consistency of the coating surface density.
[0011] As a further embodiment of the present invention, the additive is an alkyl carboxylic acid or a polyacid, including at least one of formic acid, acetic acid, propionic acid, butyric acid, oxalic acid or oxalic acid, and malonic acid.
[0012] As a further solution of the present invention, the conductive agent is a conductive carbon material, including at least one of super carbon SP, carbon nanotubes, VGCF, ks-6 or ks-16.
[0013] As a further solution of the present invention, the binder is an oily or water-based binder, including at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid.
[0014] A method for preparing a positive electrode slurry having anti-jellying properties, characterized in that it comprises the following steps: Step 1, mixing the O3 type layered oxide positive electrode material with additives, conductive agent, binder and solvent to form a slurry; Step 2, during the pulping process, the additive is used to neutralize the residual alkaline components in the pulp to inhibit the jellying phenomenon and maintain the fluidity and stability of the pulp; Step 3: evenly apply the obtained slurry on the aluminum foil and roll it to a preset thickness to form a positive electrode sheet, so that the coating surface density consistency is controlled within ±5%.
[0015] As a further solution of the present invention, the coating surface density consistency of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
[0016] A method for preparing a sodium ion battery with an anti-jellying positive electrode slurry, characterized in that it comprises the following steps: S1, uniformly coating the anti-jellying positive electrode slurry according to any one of claims 1 to 4 on an aluminum foil and rolling it to a preset thickness to obtain a positive electrode sheet; S2, mixing the negative electrode material of the sodium ion battery with the conductive agent, the binder and the solvent to form a negative electrode slurry, coating it on the aluminum foil and rolling it to a preset thickness to form a negative electrode sheet; S3, stacking or winding the positive electrode sheet, the negative electrode sheet and the separator and placing them into the battery housing; S4, the battery is injected, packaged and baked to complete the formation, ensuring that the unconsumed additives in the positive electrode slurry are completely decomposed to form a sodium-ion battery.
[0017] As a further solution of the present invention, the coating surface density consistency of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Dynamic regulation of acid-base balance and stabilization of slurry performance: This application achieves dynamic regulation of acid-base balance by adding a specific amount of organic acid additives to the positive electrode slurry, so that the acidic groups in the additives gradually react with the alkaline residual components on the surface of the positive electrode material. During the stirring, coating, rolling and other steps, the additives continuously neutralize the residual alkaline substances in the slurry to ensure that the pH value of each processing link remains within a stable range, avoiding the jelly phenomenon caused by pH fluctuations in traditional processes, and significantly improving the fluidity and operability of the slurry.
[0019] 2. Significantly improve the consistency of the pole piece coating surface density: The dynamic neutralization mechanism of the additive makes the slurry have stable viscosity and fluidity during the coating process, solving the problem of pole piece surface density deviation caused by uneven slurry in the prior art. Experiments show that the coating surface density consistency of the slurry described in this application is controlled within ±5%, thereby providing a more uniform pole piece structure for the battery and improving the battery's rate performance and capacity retention rate.
[0020] 3. Enhance battery performance and long-term stability: The additives described in this application are completely decomposed during the battery formation process and do not remain in the pole pieces or batteries, thus avoiding negative impacts on battery performance. The final internal resistance of the battery is less than 12.5 milliohms, and the capacity retention rate after 500 cycles is not less than 95%. It also maintains excellent self-discharge control performance at high temperatures, which has significant performance improvements over existing technologies. The decomposition characteristics of the additives ensure the safety and stability of the battery during long-term use, significantly improving the reliability of the technical solution of this application in sodium-ion batteries.
[0021] 4. Simplify the process flow and promote industrial application: In this application, by adding an appropriate amount of organic acid additives, the jellying of the slurry can be controlled without additional processes, which reduces the production steps and debugging difficulty, provides an economical and efficient solution for the slurry production process, and contributes to the large-scale production of sodium-ion batteries.
[0022] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1 This is a performance comparison chart of the positive electrode slurry of the present invention.
[0025] Figure 2 Graph showing the change in viscosity of the cathode slurry over time (unit: mPa•s).
[0026] Figure 3 This is a comparison chart of the density consistency of the positive electrode coating of the present invention (double-sided surface density g / m2).
[0027] Figure 4 This is a comparison chart of battery performance of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] See also Figure 1 —4. In an embodiment of the present invention, a jelly-proof positive electrode slurry is provided, wherein the positive electrode slurry is composed of an O3-type layered oxide positive electrode material, a conductive agent, a binder, a solvent and an additive, wherein the chemical formula of the positive electrode material is Na x MO 2 , 0.67 < x ≤ 1, M is at least one transition metal element including but not limited to nickel, iron, manganese, copper, titanium, and cobalt; The additive is an organic acid substance containing a carboxyl group, and its general chemical formula is R-COOH, wherein R is an alkyl group, an alkenyl group, a hydroxyl group or a keto group; The additive is added in an amount of 0.01% to 2%, preferably 0.2% to 0.5%, of the total weight of the positive electrode slurry. The additive is uniformly added to the mixed system of the O3-type layered oxide positive electrode material, the conductive agent, the binder and the solvent, so that the acidic groups in the additive gradually react with the alkaline components on the surface of the positive electrode material, thereby reducing the residual alkali content in the slurry system and maintaining the fluidity and stability of the slurry during the slurry preparation and subsequent coating process. The additive is used to maintain the acid-base balance of the slurry during the stirring and coating process, avoid the jelly phenomenon caused by pH fluctuations, and obtain a consistent surface density on the coating surface; the gradual reaction means that the acidic groups in the additive first react with the alkaline components exposed on the surface of the positive electrode material during the slurry stirring process, and then gradually react to neutralize the residual alkaline components in the slurry system during the coating and rolling process, maintaining the acid-base balance of the slurry, so as to maintain the fluidity of the slurry and the consistency of the coating surface density.
[0030] The additive is an alkyl carboxylic acid or a polyacid, including at least one of formic acid, acetic acid, propionic acid, butyric acid, oxalic acid or oxalic acid, and malonic acid; the conductive agent is a conductive carbon material, including at least one of super carbon SP, carbon nanotubes, VGCF, ks-6 or ks-16; the binder is an oily or water-based binder, including at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid.
[0031] A method for preparing a positive electrode slurry having anti-jellying properties, characterized in that it comprises the following steps: Step 1, mixing the O3 type layered oxide positive electrode material with additives, conductive agent, binder and solvent to form a slurry; Step 2, during the pulping process, the additive is used to neutralize the residual alkaline components in the pulp to inhibit the jellying phenomenon and maintain the fluidity and stability of the pulp; Step 3: evenly apply the obtained slurry on the aluminum foil and roll it to a preset thickness to form a positive electrode sheet, so that the coating surface density consistency is controlled within ±5%.
[0032] As a further solution of the present invention, the coating surface density consistency of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
[0033] A method for preparing a sodium ion battery with an anti-jellying positive electrode slurry, characterized in that it comprises the following steps: S1, uniformly coating the anti-jellying positive electrode slurry according to any one of claims 1 to 4 on an aluminum foil and rolling it to a preset thickness to obtain a positive electrode sheet; S2, mixing the negative electrode material of the sodium ion battery with the conductive agent, the binder and the solvent to form a negative electrode slurry, coating it on the aluminum foil and rolling it to a preset thickness to form a negative electrode sheet; S3, stacking or winding the positive electrode sheet, the negative electrode sheet and the separator and placing them into the battery housing; S4, the battery is injected, packaged and baked to complete the formation, ensuring that the unconsumed additives in the positive electrode slurry are completely decomposed to form a sodium-ion battery.
[0034] As a further solution of the present invention, the coating surface density consistency of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
[0035] Embodiment 1: The present invention aims at the problem that the sodium ion O3 type layered oxide positive electrode material has high residual alkali, is easy to jelly in the pulping process, has poor fluidity, and thus affects the performance of the slurry. In the pulping process, an additive containing a carboxyl group is added to neutralize the alkalinity of the positive electrode, thereby inhibiting the slurry from jellying and improving the stability of the slurry. The evaporation and decomposition of the additive can also improve the performance of the pole piece cracking, and the residual additive is decomposed during the formation, and there is no residue in the pole piece, which will not affect the performance of the battery.
[0036] The positive electrode material of sodium ion battery is O3 type layered oxide, Na x MO 2 , where 0.67<x≤1, M is one or more transition metal elements such as Ni, Fe, Mn, Cu, Ti, CO, etc.; The additive is an acidic substance containing a -COOH group, with the general formula R-COOH, where R is an alkyl group, so the additive is an alkyl acid such as formic acid, acetic acid, propionic acid, butyric acid, etc., and R is an olefinic group, so the additive is vinyl acid, acrylic acid, butenoic acid, and R is a keto group, a hydroxyl group, a carboxyl group, etc., such as oxalic acid, malonic acid, etc.; The amount of additives: 0.01%-2%, preferably: 0.2%-0.5%.
[0037] Positive electrode conductive agent: one or more of SP, ks-6, ks-16, C60, VGCF, CNTs slurry, etc. Positive electrode binder: one or more of oily or water-based binders such as PVDF, PTFE, SBR, CMC, and PAA.
[0038] Cathode solvent: NMP or water.
[0039] Negative electrode main materials: hard carbon, soft carbon, MoS, SnO2, titanium-based compounds; Negative electrode conductive agent: one or more of SP, ks-6, ks-16, C60, VGCF, CNTs slurry, etc. Negative electrode binder: one or more of oily or water-based binders such as PVDF, PTFE, SBR, CMC, and PAA; Anode solvent: NMP or water; Diaphragm: PP, PE, PP / PE / PP, polyimide, acrylic and other diaphragms; Core: stacked or wound; Sodium ion battery forms: soft pack, cylindrical, aluminum shell, heterogeneous, etc.
[0040] Comparative Example: 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of binder PVDF, and 35 parts of solvent NMP, mix well. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on a 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0041] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0042] Embodiment 2: This embodiment demonstrates the specific application process of the anti-jellying positive electrode slurry described in the present application in the preparation of positive electrode sheets for sodium ion batteries, as well as how this technical solution overcomes the defects of the prior art in actual production and obtains significant technical effects.
[0043] In the actual preparation of sodium ion battery positive electrode slurry, O3 type layered oxide Na x MO 2 (0.67 < x≤ 1, M is nickel, iron, manganese) as the positive electrode material, this material has high capacity and good cycle stability in the field of sodium ion batteries. However, due to the problem of alkaline residue during the calcination process, the slurry is very easy to jelly during the preparation process, resulting in poor fluidity and affecting the uniformity of the electrode coating. To solve this problem, in this embodiment, an organic acid additive containing a carboxyl group (-COOH) is added to the positive electrode slurry to neutralize the alkaline components. The specific additive is acetic acid, and the addition amount is controlled at 0.2% of the total weight of the positive electrode slurry.
[0044] Specific steps: 1. Slurry mixing and acid-base neutralization: In the stirring equipment, mix the positive electrode material Na X MO 2Mixed with acetic acid additive, conductive agent (carbon nanotubes), binder (polyvinylidene fluoride PVDF) and solvent NMP. Acetic acid, as a carboxyl-containing organic acid, reacts with alkaline residues in the positive electrode material. By gradually releasing acidic groups, the additive continuously neutralizes the alkaline components during the entire stirring process to avoid the jelly phenomenon caused by the acid-base imbalance of the slurry. The additive is evenly dispersed in the slurry, so that the slurry maintains good fluidity and is easy to operate.
[0045] 2. Coating and surface density consistency control: The prepared positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 microns, and the coating density is set to 150g / m². After coating, a rolling operation is performed to roll the pole piece to a thickness of 120 microns. During this process, due to the acid-base balance regulation effect of the additive, the slurry viscosity is maintained in a relatively stable range, the pole piece coating process is smooth, and the problem of uneven surface density caused by cause freezing is avoided. After testing, the consistency of the coating surface density of the positive electrode sheet of this embodiment is controlled within ±5%, which is significantly better than the traditional slurry that does not use the technology of this application.
[0046] 3. High-temperature formation and battery performance testing: The prepared positive electrode plates, negative electrode materials (hard carbon) and diaphragm stacks are assembled into the sodium-ion battery housing. After the injection and packaging are completed, the formation treatment is carried out in a high-temperature environment. During this process, the acetic acid additive in the positive electrode slurry is further decomposed without producing residues or by-products, ensuring that there is no additive residue on the surface of the pole piece. After 500 cycles, the assembled sodium-ion battery has a capacity retention rate of 95%, and the internal resistance is stable below 12 milliohms, showing good rate discharge performance.
[0047] In this embodiment, the dynamic neutralization of organic acid additives effectively controls the acid-base balance of the slurry during the preparation process, avoiding the 2 CO 3 The jelly problem of slurry caused by residue. The gradual release mechanism of acetic acid ensures the fluidity and stability of the slurry during stirring, coating and rolling, and significantly improves the surface density consistency of the electrode coating. Comparative experiments show that the slurry coating surface density of the control group without the additive has obvious deviation, and the electrode has a decrease in capacity and an increase in resistance during the cycle. The sodium ion battery using the slurry of this embodiment shows higher cycle stability and better rate discharge performance.
[0048] Embodiment 3: 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of binder PVDF and 0.2 parts of oxalic acid, 35 parts of solvent NMP, mix well. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on a 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0049] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0050] Embodiment 4: This embodiment demonstrates the specific implementation of the anti-jellying positive electrode slurry of the present application in the application of high energy density sodium ion batteries, and further demonstrates the actual effect of this technical solution in improving battery performance and extending service life.
[0051] In the production of sodium ion batteries, the sodium ion positive electrode material is usually layered oxide Na x MO 2 (where M is a transition metal such as nickel, iron, or manganese) and has high energy density and excellent rate performance. 2 CO 3 The presence of residual alkaline components such as iodine significantly increases the pH value of the slurry during the slurry making process, causing the positive electrode slurry to easily become jelly-like. This phenomenon not only affects the fluidity of the slurry and the uniformity of coating, but also affects the surface density consistency of the electrode after coating, seriously reducing the rate discharge performance and cycle life of the battery.
[0052] To solve this problem, the carboxyl-containing organic acid additive described in this application is used in this embodiment, and the dosage and addition order are optimized to achieve a good effect of inhibiting jelly formation and improving slurry stability. Specifically, oxalic acid is used as an additive, and the addition amount is 0.5% of the total weight of the positive electrode slurry.
[0053] Implementation steps: 1. Preparation of positive electrode slurry: In a high-speed stirring device, 95 parts of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 The positive electrode material, 1.5 parts of conductive carbon (ks-6) and 2 parts of carbon nanotube (CNTs) conductive agent, 2 parts of polyvinylidene fluoride (PVDF) binder, 35 parts of NMP solvent and 0.5 parts of oxalic acid additive were added in sequence and stirred until uniform. The introduction of oxalic acid gradually neutralizes the alkaline substances NaOH and Na remaining on the surface of the positive electrode material during the slurry preparation process. 2 CO 3 , effectively preventing the slurry from becoming jelly. In the early stage of stirring, the carboxyl group of oxalic acid is gradually released and reacts with the residual alkali, so that the acid-base balance of the slurry remains stable, ensuring that the slurry maintains fluidity before coating.
[0054] 2. Pole sheet coating and rolling: The prepared positive electrode slurry is evenly coated on a 12-micron thick aluminum foil, and the coating density is controlled at 150g / m². The coated pole sheet is then rolled to a thickness of 120 microns. Due to the acid neutralization effect of the oxalic acid additive, the viscosity of the slurry remains uniform during the coating process, avoiding the stratification phenomenon caused by acid-base imbalance, and significantly improving the surface density consistency of the pole sheet coating. After testing, the double-sided surface density of the coated pole sheet is controlled within the range of ±5%, ensuring the consistency of the battery performance after assembly.
[0055] 3. Battery assembly and performance testing: The prepared positive electrode plates are matched with the hard carbon plates of the negative electrode materials, and are wound after being stacked with PE diaphragms, loaded into aluminum shell batteries, and injected with electrolyte. After completing the packaging and high-temperature formation steps, the oxalic acid additive is completely decomposed during the formation process, without producing residues or by-products, ensuring the purity of the battery. The assembled sodium-ion battery was subjected to rate discharge tests and cycle life tests. The results showed that the capacity retention rate at a 5C rate was 93.6%, the internal resistance was 12 milliohms, and the self-discharge rate was controlled within 3% after being stored at a high temperature of 45°C for 7 days. The capacity retention rate was not less than 95% after 500 cycles.
[0056] The technical solution of this embodiment effectively realizes the dynamic regulation of acid-base balance, and suppresses the jellying phenomenon of the slurry caused by excessively high pH value in the traditional process. The oxalic acid additive continuously neutralizes the residual alkali during the slurry preparation and coating process, so that the fluidity, stability and coating surface density consistency of the slurry are significantly improved, ensuring the structural uniformity of the electrode. At the same time, the complete decomposition of oxalic acid avoids the problem of residues in the finished battery, so that the internal resistance and self-discharge performance of the battery are maintained at an excellent level. This embodiment shows that the technical solution of the present application has achieved a significant improvement in battery performance and consistency in the application of sodium-ion battery positive electrode slurry, is suitable for large-scale production, and further expands the practical application potential of sodium-ion batteries.
[0057] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A jelly-proof positive electrode slurry, the positive electrode slurry is composed of an O3-type layered oxide positive electrode material, a conductive agent, a binder, a solvent and an additive, wherein the chemical formula of the positive electrode material is Na x MO2, 0.67 < x ≤ 1, M is at least one transition metal element including but not limited to nickel, iron, manganese, copper, titanium, and cobalt; characterized in that: The additive is an organic acid substance containing a carboxyl group, and its general chemical formula is R-COOH, wherein R is an alkyl group, an alkenyl group, a hydroxyl group or a keto group; The additive is added in an amount of 0.01% to 2%, preferably 0.2% to 0.5%, of the total weight of the positive electrode slurry. The additive is uniformly added to the mixed system of the O3-type layered oxide positive electrode material, the conductive agent, the binder and the solvent, so that the acidic groups in the additive gradually react with the alkaline components on the surface of the positive electrode material, thereby reducing the residual alkali content in the slurry system and maintaining the fluidity and stability of the slurry during the slurry preparation and subsequent coating process. The additive is used to maintain the acid-base balance of the slurry during the stirring and coating process, avoid the jelly phenomenon caused by pH value fluctuation, and obtain a consistent surface density on the coating surface.
2. The anti-jellying positive electrode slurry according to claim 1, characterized in that: The stepwise reaction means that the acidic groups in the additives first react with the alkaline components exposed on the surface of the positive electrode material during the slurry stirring process, and then gradually react to neutralize the residual alkaline components in the slurry system during the coating and rolling process to maintain the acid-base balance of the slurry, so as to maintain the fluidity of the slurry and the consistency of the coating surface density.
3. The anti-jellying positive electrode slurry according to claim 1, characterized in that: The additive is an alkyl carboxylic acid or a polyacid, including at least one of formic acid, acetic acid, propionic acid, butyric acid, oxalic acid or oxalic acid and malonic acid.
4. The anti-jellying positive electrode slurry according to claim 1, characterized in that: The conductive agent is a conductive carbon material, including at least one of super carbon SP, carbon nanotubes, VGCF, KS-6 or KS-16.
5. The anti-jellying positive electrode slurry according to claim 1, characterized in that: The binder is an oily or water-based binder, including at least one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid.
6. A method for preparing a positive electrode slurry having anti-jellying properties, characterized in that: The following steps are involved: Step 1, mixing the O3 type layered oxide positive electrode material with additives, conductive agent, binder and solvent to form a slurry; Step 2, during the pulping process, the additive is used to neutralize the residual alkaline components in the pulp to inhibit the jellying phenomenon and maintain the fluidity and stability of the pulp; Step 3: evenly apply the obtained slurry on the aluminum foil and roll it to a preset thickness to form a positive electrode sheet, so that the coating surface density consistency is controlled within ±5%.
7. A sodium ion battery with an anti-jellying positive electrode slurry according to claim 6, characterized in that: The density consistency of the coating surface of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
8. A method for preparing a sodium ion battery having an anti-jellying positive electrode slurry, characterized in that: The steps include: S1, uniformly coating the anti-jellying positive electrode slurry according to any one of claims 1 to 4 on an aluminum foil and rolling it to a preset thickness to obtain a positive electrode sheet; S2, mixing the sodium ion battery negative electrode material with the conductive agent, the binder and the solvent to form a negative electrode slurry, coating it on the aluminum foil and rolling it to a preset thickness to form a negative electrode sheet; S3, stacking or winding the positive electrode sheet, the negative electrode sheet and the separator and placing them into the battery housing; S4, the battery is injected, packaged and baked to complete the formation, ensuring that the unconsumed additives in the positive electrode slurry are completely decomposed to form a sodium-ion battery.
9. The method for preparing a sodium ion battery with an anti-jellying positive electrode slurry according to claim 8, characterized in that: The density consistency of the coating surface of the positive electrode sheet of the sodium ion battery is controlled within ±5%, and the internal resistance is lower than 12.5 milliohms to have excellent rate discharge performance.
Citation Information
Patent Citations
Positive electrode slurry for sodium ion battery and preparation method for positive electrode slurry
CN106602071A
Cathode piece of lithium ion battery and preparation method of cathode piece
CN108336300A
Sodium-ion battery positive electrode slurry and preparation method thereof
CN114497521A
Positive plate processing technology of sodium ion battery and positive plate
CN116722105A
Sodium-ion battery positive electrode slurry and preparation method thereof
CN118486825A